Ekspresi HPV16 Onkoprotein E7 pada Lesi Prakanker dan Karsinoma Sel Skuamosa Serviks - Wresnindyatsih; Verli Saniba; Zulkarnain Musa; Zen Hafy (Majalah Patologi Indonesia, 2020)
BackgroundCervical cancer is the secondmost common malignancy in women worldwide.The vast majority of cervical cancersare associatedwith high risk HPV16 infection. The persistence of HPV16 and integration of viral DNA into cell genome are necessary for thedevelopment of precancerous lesion and squamous cell carcinoma (SCC) of the cervix. The integration of viral DNA in the host cellgenome resulted in the regulation of oncoprotein E7 leading to detection of HPV16 E7 expression in precancerous lesions and SCCof the cervix.The aim of this study was to evaluate differences of HPV16 E7 expression in precancerous lesions and cervical SCC.MethodsAn observational study with cross-sectional design was performedat Department of Anatomical Pathology Faculty of MedicineUniversity of Sriwijaya/dr. Mohammad Hoesin General Hospital Palembang, from 1st July 2014 to 30st Juni 2017. The selectedsamples consisted of 25 precancerous cases lesions (13 cases of LSIL and 12 samples of HSIL) and SCC (25 cases).Immuhistochemical stained was conducted using HPV16 E7 antibody. Fisher exact’s test was used to analyze differences inexpression of HPV16 E7 among precancerous lesions and cervical SCC.ResultsThe pracancerous lesions occurred mostly between the ages of 30-40 years, while SCC were those between the ages of 51-60years. All SCC cases (100%) and 91.6% of HSIL showed weak to strong HPV16 E7 expression, and 84.6% cases of LSIL showedimmunonegative.ConclusionThe positivity of HPV16 E7 increased in HSIL and KSS lesions.